Global Innovation Trends and Georgia - Shaburishvili, Shota; Chania, Maia (European Journal of Economics and Business Studies, 2017)
Continuous and progressive technological changes based on scientific-technical revolution have become common under modern globalization processes. They gradually destroy the traditional distinction between low and high-tech sectors and shift the general vector of development of the country from static, temporary comparative advantages to innovation-based dynamic competitive advantage. In other words, innovation is becoming a significant resource that determines a competitive advantage of a country and is essential for achieving efficient and rapid improvement of welfare of a society. What is business innovation? How does innovationinfluence business development and its management in the country? In modern global business management success can’t be achieved without application and proper management of up-to-date technologies. As a result, in recent years, scientists have paid special interest to the importance of technology and scientific and technological progress in business development.
Keywords: Innovation; Science; Technology; Research; development; Competitive Advantage